Application of Automated Irrigation Systems in Tobacco Seedling Management in Galis Village (Karapan Network Journal : Journal Computer Technology and Mobile Ad Hoc Network, 2025)
Tobacco seedling cultivation is a crucial stage in tobacco farming because it determines the quality and productivity of plants in the next phase. In Galis Village, the seedling process is still carried out conventionally, characterized by manual watering, unmeasured environmental monitoring, and inefficient use of water and labor. The development of the Internet of Things (IoT) offers a new approach to agricultural management through automation and data-based environmental monitoring. This study aims to implement and evaluate an IoT-based automatic watering system in tobacco seedling management to improve the efficiency of water use and farmers' working time. This study uses a design and field trial method with a quantitative and qualitative approach. The system was developed using a microcontroller integrated with soil moisture sensors, air temperature and humidity sensors, rain sensors, a time scheduling module, and Telegram-based notifications. Testing was conducted through observation of system performance, measurement of response time, and comparison of water usage and working time before and after system implementation. The results of the study show that the system is able to work stably and responsively. Watering can be automated based on soil moisture conditions and stopped when rain is detected. The system has successfully reduced water usage by around 35% and reduced farmers' manual labor time by around 45%. The notification delivery delay time is in the range of 2–5 seconds, which is still effective for real-time monitoring. The IoT-based automatic irrigation system has proven effective in improving the efficiency and ease of tobacco seedling management. Further research is recommended to develop the system on a larger scale and add integration of historical data analytics.
Keywords: Keywords: Internet of Things, Automatic Irrigation, Tobacco Nursery, Smart Agriculture, Water Efficiency